2021
DOI: 10.3390/healthcare9080936
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Foot Status and Motor Status in Preschool Children: A Simple, Comparative Observational Study

Abstract: Background: The research objective of the study is to determine the differences in the manifestation of the motor status of normally fed preschool test subjects, classified into groups according to foot status. Methods: This is a simple, comparative observational study. Preschool children included in this study have been subjected to anthropometric measurements in order to determine BMI, tests for motor skills assessment (running at 20 m from a high start, standing broad jump, backwards polygon, rectangular se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Statistically significant differences were noted by the authors in the 20 m run and the ball throw. Similar conclusions were presented by Kojić et. al (2021) based on research on Serbian children.…”
Section: Discussionsupporting
confidence: 92%
“…Statistically significant differences were noted by the authors in the 20 m run and the ball throw. Similar conclusions were presented by Kojić et. al (2021) based on research on Serbian children.…”
Section: Discussionsupporting
confidence: 92%
“…The influence of weight status on performance in motor skills and fitness tests was examined [ 25 , 26 , 31 ], as was the relationship between physical activity, sedentary behavior, body composition, and fitness [ 23 , 24 , 29 ]. Some studies also described norms or percentiles for motor development scores relative to anthropometric measures [ 22 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hwang et al [ 27 ] found that physical activity was a common predictor of higher BMI in children with and without motor delay. For instance, Kojić et al [ 28 ] reported significant differences in motor status among preschoolers with varying foot statuses, suggesting that even subtle variations in physical characteristics can impact motor skill development. Collectively, these findings emphasize the importance of early identification and intervention for children with impaired growth, development, or specific conditions that may affect their physical fitness and motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…From a biomechanical perspective, foot status has been shown to signi cantly impact motor performance, including jumping, running, or hopping, in preschool children, according to an observational study [30]. Hence, using foot insoles is a standard non-surgical method to correct lower extremity biomechanics in children.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, using foot insoles is a standard non-surgical method to correct lower extremity biomechanics in children. It was observed that children with at foot performed the worst in motor assessments, followed by those with standard arch foot and high arch foot [30]. In a study by Selby-Silverstein et al, foot orthotics were used in children aged 3 to 6 years with Down syndrome, and it was found that the variability of gait parameters and walking speed decreased compared to participants without Down syndrome [31].…”
Section: Discussionmentioning
confidence: 99%